Improving Stroke Measure Compliance and Outcomes Through Hospital Collaboration. Issue 4 (27th February 2023) - Moore, Kari D.; Summers, Debbie; Wilson, Susan E.
Abstract : Globally, national stroke registries have been shown to improve the quality of patient care and outcomes. However, registry utilization and implementation vary by country. In the United States, stroke-specific performance measures must be met to achieve and maintain stroke center certification awarded by the state or nationally accredited certifying bodies. The 2 stroke registries available in the United States are the American Heart Association Get With The Guidelines-Stroke registry, which is voluntary, and the Paul Coverdell National Acute Stroke Registry, funded competitively to states by the Centers for Disease Control and Prevention. Compliance with stroke processes of care is variable, and quality improvement initiatives among organizations have been shown to have an impact on improving stroke care delivery. However, the effectiveness of interorganizational continuous quality improvement approaches, especially among competing institutions, to improving stroke care is ambiguous, and no uniform governance for successful interhospital collaboration has been identified. The purpose of this article is to review national initiatives focused on interorganizational collaboration to improve stroke care delivery with a focus on interhospital collaboration in the United States to improve stroke performance measures specific to stroke center certification. The state of Kentucky's experience and utilization of the Institute for Healthcare Improvement Breakthrough Series model with key strategies for success will be discussed to serve as a foundation and empower novice stroke leaders in learning health systems. The models may be adapted internationally for application to stroke-specific care process improvement locally, regionally, and nationally; among organizations within the same health system or competing systems; and among organizations with funding or without funding to improve stroke performance measures.